The Impact of Macroeconomic Variables, Financing Risks, and Third-Party Funds on Islamic Banking's Profitability - Astuti, Retno Puji; Nurhasanah (Economics & Islamic Finance Journal (ECIF), 2024)
The aim of this research was to examine the impact of macroeconomic variables, financing risks , and third-party funds on the profitability of Islamic banking.  The GDP and inflation are the macroeconomic variables that are taken into effect. Non-performing financing (NPF) is the financial risk that is used. Islamic banks that are registered with the Financial Services Authority (OJK) for the 2019–2020 sample period represent the research population. Purposive sampling was the technique used, and the sample size consisted of fourteen Islamic banks. This study used Eviews 10 to do mutivariate regression analysis as its data analysis tool. The findings showed that the GDP and inflation, two macroeconomic variables, had no impact on the profitability of Islamic banking. Profitability is significantly impacted by third party funds, whereas Islamic banking's profitability is significantly impacted negatively by NPF.